The Third Dimension of Ferroelectric Domain Walls. Issue 36 (5th August 2022) - Roede, Erik D.; Shapovalov, Konstantin; Moran, Thomas J.; Mosberg, Aleksander B.; Yan, Zewu; Bourret, Edith; Cano, Andres; Huey, Bryan D.; van Helvoort, Antonius T. J.; Meier, Dennis
Abstract: Ferroelectric domain walls are quasi‐2D systems that show great promise for the development of nonvolatile memory, memristor technology, and electronic components with ultrasmall feature size. Electric fields, for example, can change the domain wall orientation relative to the spontaneous polarization and switch between resistive and conductive states, controlling the electrical current. Being embedded in a 3D material, however, the domain walls are not perfectly flat and can form networks, which leads to complex physical structures. In this work, the importance of the nanoscale structure for the emergent transport properties is demonstrated, studying electronic conduction in the 3D network of neutral and charged domain walls in ErMnO3 . By combining tomographic microscopy techniques and finite element modeling, the contribution of domain walls within the bulk is clarified and the significance of curvature effects for the local conduction is shown down to the nanoscale. The findings provide insights into the propagation of electrical currents in domain wall networks, reveal additional degrees of freedom for their control, and provide quantitative guidelines for the design of domain‐wall‐based technology. Abstract : Tomographic microscopy techniques are applied to image the 3D network of ferroelectric domain walls in ErMnO3 with nanoscale spatial resolution. The study reveals how electrical currents propagate through the domain wall network and demonstrates the importance of local corrugation phenomena for the electronic transport behavior.